DETERMINATION X-BAND RADAR REFLECTIVITY THRESHOLD VALUE of HAIL INCIDENCE IN BANDUNG (Case Study April 1th â May 4th 2017) - Yanti, Rahma
There is no research on the value of the reflectivity threshold to detect the incidence of hail in Bandung with X-Band radar. Many methods have been developed for the detection of hail using radar and there are different methods that are suitable for different regions. Therefore, to overcome these problems, the determination and analysis of the appropriate X-Band radar threshold will be carried out in Bandung. In this study the data used are radar data as primary data in the determination and analysis, hail report data as a determinant of the time of hail events, satellite data as a determinant of cloud top temperature, Era-Interim data as a determinant of altitude when the temperature is 0°C and -20°C, and rainfall data for determining non-hail events and further analysis. The method used is to calculate and determine the ability to detect hail in the CAPPI, Auer, Wadvogel, VIL, and POSH methods. The results of the processing of radar reflectivity data indicate that there is a high reflectivity value in the event of hail and non-hail at low altitudes. The existence of high reflectivity values in the event of hail has a span of <30 minutes while nonhail can last up to> 1 hour. The appearance of this high reflectivity in hail occurs after clouds grow vertically while high reflective in non-hail starts from low altitude and seems to grow vertically upwards. The results of the comparative analysis show that the Waldvogel method can detect the occurrence of hail better than all methods because it can see how the growth of cloud height is happening. However, the use of this method needs to review the extent of clouds that occur as a differentiator of two events, because in the event of non-hail clouds grow wider than hail. Further evaluation of the threshold values in the CAPPI, VIL, and POSH methods resulted in different threshold values for Bandung.